2022
DOI: 10.1073/pnas.2206931119
|View full text |Cite
|
Sign up to set email alerts
|

Leisure-time sedentary behaviors are differentially associated with all-cause dementia regardless of engagement in physical activity

Abstract: Sedentary behavior (SB) is associated with cardiometabolic disease and mortality, but its association with dementia is currently unclear. This study investigates whether SB is associated with incident dementia regardless of engagement in physical activity (PA). A total of 146,651 participants from the UK Biobank who were 60 years or older and did not have a diagnosis of dementia (mean [SD] age: 64.59 [2.84] years) were included. Self-reported leisure-time SBs were divided into two domains: time spent watching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 70 publications
4
17
0
1
Order By: Relevance
“…These study results complement previous work suggesting increased time in sedentary behavior is associated with reduced cognitive performance, 20 and that some types of leisure-time sedentary behavior (eg, cognitively passive TV watching) are associated with increased dementia risk. 7…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These study results complement previous work suggesting increased time in sedentary behavior is associated with reduced cognitive performance, 20 and that some types of leisure-time sedentary behavior (eg, cognitively passive TV watching) are associated with increased dementia risk. 7…”
Section: Discussionmentioning
confidence: 99%
“…Previous work found that self-reported leisure-time sedentary behaviors were associated with risk of developing all-cause dementia, and the direction of the risk depended on the activity done while sedentary (ie, cognitively passive TV watching vs cognitively active computer use) . However, a recent study using accelerometer-derived sitting time did not find an association between sedentary behaviors and incident dementia in a sample of older women (n = 1277) …”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…A recent study has reported that time spent watching TV was associated with increased risks of incident dementia and time spent using a computer was associated with decreased risks of incident dementia. Reducing the cognitively passive SB times (i.e., TV) and increasing time spent on cognitively active SB activities (i.e., computer) may be effective behavioral modification targets for reducing the risk of dementia [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“… In einer weiteren US-amerikanischen Studie zeigte sich erneut, dass das Sitzen vor dem Fernsehapparat, nicht jedoch das Sitzen vor dem Computer, die Wahrscheinlichkeit einer Demenz erhöht 36 . …”
unclassified